Aliphatic polyesters and their use

JP2026149515A5Pending Publication Date: 2026-10-30KINGFA SCI & TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026037602
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-10
Filing Date
2026-03-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

Conventional wrap films made from polyethylene, biaxially oriented polyester films, and chlorinated polypropylene are non-biodegradable, leading to 'white pollution, and biodegradable alternatives like PBAT suffer from slow crystallization, high viscosity, film breakage, and food contact risks due to lubricant migration.

Method used

An aliphatic polyester with controlled oligomer content and molar ratios of succinic and sebacic acid residues, combined with specific processing conditions, to achieve good unwindability, food safety, and biodegradability.

Benefits of technology

The aliphatic polyester provides packaging films with excellent unwindability, reduced food contact risk, and effective biodegradability, meeting composting requirements while maintaining processing stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention aims to provide aliphatic polyesters and their uses. [Solution] The present invention provides an aliphatic polyester and its use. The aliphatic polyester comprises a dibasic acid residue and a diol residue, wherein the dibasic acid residue comprises, as residues, 65-90 mol% succinic acid residues based on a total mole fraction of 100 mol% of a1) and a2), and 10-35 mol% sebacic acid residues based on a total mole fraction of 100 mol% of a1) and a2), the diol residue is selected from at least an equimolar amount of 1,4-butanediol residues with respect to the dibasic acid residue, the aliphatic polyester contains oligomers with a number average molecular weight <1000 as measured by GPC, and the mass fraction of oligomers with a number average molecular weight <1000 as measured by GPC is 0.08-3.5 wt%. Packaging films made from the aliphatic polyester combine good food contact and unwinding properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention belongs to the technical field of polyester materials, and specifically relates to an aliphatic polyester and uses thereof. [Background Art]

[0002] Wrap film is a plastic packaging film product that can not only extend the shelf life of food, but also retain moisture in stored food and maintain its freshness. More importantly, when used on opened beverages, fruits, tableware and the like, it also plays a role in isolating bacteria, which can improve hygiene and safety. Therefore, wrap film is widely used in household use, supermarkets, industrial food packaging, and the like. However, conventional wrap films mainly employ polyethylene films, biaxially oriented polyester films (BOPET), biaxially oriented polypropylene films (BOPP), chlorinated polypropylene films (CPP), and the like. These wrap films are not biodegradable, and have the problem of being extremely prone to causing "white pollution" when discarded.

[0003] To address the problem of conventional wrap films being difficult to decompose, biodegradable polyesters such as polybutylene adipate terephthalate (PBAT) have been used as substitutes for the aforementioned conventional film materials, improving the decomposition properties of wrap films. However, PBAT resin has a slow crystallization rate due to the entanglement of its molecular chains, and its high viscosity makes it prone to sticking to stainless steel rollers during the casting process, leading to frequent film breakage and affecting processing stability. At the same time, the high viscosity of the film makes the manufactured wrap film difficult to unwind and prone to bending during use, degrading the user experience. To reduce the viscosity of PBAT resin and improve unwindability, conventional techniques often involve blending lubricants such as epoxidized soybean oil into PBAT to improve the unwindability of PBAT wrap films. However, because the lubricants and PBAT resin have different polarities, migration precipitation is likely to occur during use, increasing the risk of contact with food.

[0004] Based on this, the development of biodegradable wrap films that combine good rewindability with a low risk of food contact is an urgent issue that needs to be addressed in this field. [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] The present invention aims to provide an aliphatic polyester and its use in order to overcome the shortcomings of the prior art. The aliphatic polyester is used in the manufacture of packaging films, particularly food packaging films, and solves the problem in the prior art in that packaging films cannot combine good unwinding properties and food contact properties, while simultaneously exhibiting good biodegradability and meeting requirements such as composting at home. [Means for solving the problem]

[0006] To achieve its objective, the present invention employs the following technical solutions.

[0007] In a first aspect, the present invention provides an aliphatic polyester comprising a dibasic acid residue and a diol residue, wherein the dibasic acid residue comprises, as residues, 65 to 90 mol% succinic acid residues based on a total mole fraction of 100 mol% of a1) and a2), and 10 to 35 mol% sebacic acid residues based on a total mole fraction of 100 mol% of a1) and a2), the diol residue is selected from at least an equimolar amount of 1,4-butanediol residues with respect to the dibasic acid residue, the aliphatic polyester contains oligomers with a number average molecular weight < 1000 as measured by GPC, and the mass fraction of oligomers with a number average molecular weight < 1000 as measured by GPC in the aliphatic polyester is 0.08 to 3.5 wt%.

[0008] In this invention, succinic acid and / or succinic acid derivatives are introduced into the molecular chain of the polyester through a polymerization reaction to form succinic acid residues. Sebacic acid and / or sebacic acid derivatives are introduced into the molecular chain of the polyester through a polymerization reaction to form sebacic acid residues. Polybutylene succinate sebacate, formed from succinic acid and / or its derivatives, sebacic acid and / or its derivatives, and 1,4-butanediol, has good biodegradability and can meet the requirements for composting at home. However, when succinic acid and sebacic acid react with 1,4-butanediol, oligomers with a degree of polymerization of 1 to 8 are very readily formed, resulting in an excessively high oligomer content (>4 wt%) in the resulting aliphatic polyester. When in contact with acidic or alcohol-containing foods, the oligomers are prone to migration and precipitation, creating a food contact risk. Therefore, those skilled in the art tend to reduce the oligomer content, but the inventors have discovered that the presence of oligomers during processing is advantageous because it provides good lubrication, reduces the viscosity of the system, and gives the manufactured packaging film good unwindability. Accordingly, the present invention controls the molar ratio of succinic acid residues to sebaciate residues in polybutylene succinate sebacate and controls the oligomer content in aliphatic polyester to a specific range, thereby enabling the packaging film manufactured from the aliphatic polyester to possess good unwindability and food contact properties, while simultaneously having good degradability, thus meeting requirements such as composting at home.

[0009] The term "residue" refers to any organic structure introduced into the polymer molecular chain by related monomers through polycondensation reactions, i.e., an organic structure derived from related monomers. For example, a dibasic acid residue refers to a structure derived from a dibasic acid monomer in an aliphatic polyester.

[0010] In the present invention, the succinic acid derivative includes an alkyl succinate, and exemplary the alkyl succinate may be at least one of dimethyl succinate, diethyl succinate, di-n-propyl succinate, diisopropyl succinate, di-n-butyl succinate, diisobutyl succinate, di-tert-butyl succinate, di-n-pentyl succinate, diisopentyl succinate, and di-n-hexyl succinate. The alkyl succinate may be an alkyl ester formed from succinic acid, or an alkyl ester formed from succinic anhydride, and preferably dimethyl succinate formed from succinic anhydride.

[0011] In the present invention, the sebacate derivative comprises an alkyl sebacate, and exemplary the alkyl sebacate may be at least one of dimethyl sebacate, diethyl sebacate, di-n-propyl sebacate, diisopropyl sebacate, di-n-butyl sebacate, diisobutyl sebacate, di-tert-butyl sebacate, di-n-pentyl sebacate, diisopentyl sebacate, or di-n-hexyl sebacate. The alkyl sebacate may be an alkyl ester formed from sebacate or an alkyl ester formed from sebacate anhydride.

[0012] In the present invention, the oligomers include linear or cyclic polyester oligomers produced by the reaction of a dibasic acid with a diol, and also include cyclic oligomers produced by the thermal decomposition of a prepolymer or polycondensed polymer during the prepolymerization and polycondensation process, resulting in "backbiting" of the terminal groups.

[0013] In this invention, the oligomer content can be tested using gel permeation chromatography (GPC).

[0014] Preferably, the oligomer in the aliphatic polyester has the following characteristics: 0.05wt%<q1<1.0wt%, 0.1wt%<q2<2.5wt%, wherein q1 is the mass fraction of oligomers with a number average molecular weight of less than 500 in the aliphatic polyester measured by GPC, q2 is the mass fraction of oligomers with a number average molecular weight of less than 1000 in the aliphatic polyester measured by GPC, and more preferably 0.08wt%<q1<0.8wt% and 0.15wt%<q2<2.1wt%.

[0015] Preferably, q1 is 0.1 to 0.6 wt%.

[0016] Preferably, q2 is 0.2 to 1.3 wt%.

[0017] Preferably, the ratio of q2 to q1 is <2, more preferably the ratio of q2 to q1 is <1.5, and still more preferably the ratio of q2 to q1 is 1.1 to 1.45.

[0018] Preferably, the dibasic acid residues comprise, as residues, 70 to 87 mol% of succinic acid residues based on 100 mol% of the total molar fraction of a1): a1) and a2), and 13 to 30 mol% of sebacic acid residues based on 100 mol% of the total molar fraction of a2): a1) and a2); more preferably, the dibasic acid residues comprise, as residues, 74 to 85 mol% of succinic acid residues based on 100 mol% of the total molar fraction of a1): a1) and a2), and 15 to 26 mol% of sebacic acid residues based on 100 mol% of the total molar fraction of a2): a1) and a2).

[0019] In the present invention, in consideration of the aging resistance, hydrolysis resistance, degradability, cost and the like of the aliphatic polyester, preferably, in accordance with GB / T 32366-2015, the carboxyl content of the aliphatic polyester is <40mol / t, more preferably the carboxyl content is <30mol / t, still more preferably the carboxyl content is <22mol / t, and particularly preferably the carboxyl content is 8 to 20mol / t.

[0020] In this invention, the carboxyl content can be controlled by adjusting the degree of reactivity or suppressing thermal decomposition by changing conditions such as the ratio of alcohol to acid, polymerization temperature, and polymerization time. Furthermore, the carboxyl content can also be controlled by suppressing the type and amount of impurities in the raw materials, such as nitrogen compounds and metal ions.

[0021] Taking into consideration production efficiency and the mechanical properties of the molded article, preferably, in accordance with GB / T 17931-1999, the intrinsic viscosity of the aliphatic polyester is 1 to 3 dL / g, more preferably 1.5 to 2.2 dL / g, more preferably 1.58 to 2.11 dL / g, more preferably 1.67 to 2.02 dL / g, and particularly preferably 1.82 to 1.95 dL / g.

[0022] In the present invention, the method for producing the aliphatic polyester is not particularly limited, and any method capable of producing an aliphatic polyester having the specific oligomer content of the present invention is acceptable. Preferably, the method for producing the aliphatic polyester is Step (1) involves reacting a dibasic acid with a diol to obtain an esterification product, Step (2) involves subjecting the esterification product obtained in step (1) to a prepolymerization reaction to obtain a prepolymerization product, Step (3) involves subjecting the prepolymerization product obtained in step (2) to a polycondensation reaction to obtain the polycondensation product, The process includes step (4), which involves contacting the polycondensation product from step (3) with an organic solvent to obtain the aliphatic polyester.

[0023] In the present invention, the dibasic acid in step (1) is succinic acid and / or a succinic acid derivative, and sebacic acid and / or a sebacic acid derivative. The dibasic acid may be used alone or as a mixture of at least two. The diol is 1,4-butanediol.

[0024] In the present invention, the origin of the succinic acid and / or succinic acid derivative is not particularly limited. It may be bio-based succinic acid and / or succinic acid derivative (that is, the raw material for production is biomass resource), or may be petroleum-based succinic acid and / or succinic acid derivative (that is, the raw material for production is petroleum resource).

[0025] In the present invention, the molar ratio of the diol to the dibasic acid in step (1) may be (1.2 to 3):1, for example, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, or a range between any of the above numerical values, and more preferably (1.4 to 2):1.

[0026] In the present invention, the raw materials for the reaction in step (1) further comprise a crosslinking agent. Based on 100 wt% of the total mass of the dibasic acid and the diol, the mass of the crosslinking agent is 0 to 3 wt%. The crosslinking agent comprises at least one selected from polyols, polybasic acids and polybasic acid anhydrides. Illustratively, the crosslinking agent includes, but is not limited to, tartaric acid, citric acid, malic acid, trimethylolpropane, trimethylolethane, pentaerythritol, polyether triol, glycerol, trimesic acid, trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic dianhydride, and the like.

[0027] In the present invention, the reaction in step (1) comprises an esterification reaction and / or a transesterification reaction. The reaction is carried out at a temperature of 140 to 220°C, a pressure of 0.7 to 1.4 bar, and a reaction time of 2 to 5 hours; more preferably, the reaction is carried out at a temperature of 165 to 212°C, a pressure of 0.78 to 1.2 bar, and a time of 2.4 to 4.5 hours.

[0028] In the present invention, step (1) may be carried out in one mixing device: after the dibasic acid and the diol are mixed to obtain a slurry, the temperature is raised to allow the reaction to proceed.

[0029] In the present invention, the carboxyl content of the esterification product in step (1) is 245 to 575 mol / t, more preferably 310 to 420 mol / t.

[0030] In this invention, after the reaction in step (1), the present invention further includes a step of removing excess diol by distillation, and the removed diol can be recycled as a raw material after purification by distillation. The purity of the purified diol is ≥95%.

[0031] In the present invention, the preliminary polymerization reaction in step (2) is carried out at a temperature of 230 to 260°C, a pressure of 0.3 to 0.8 bar, and for a duration of 70 to 200 mins, and more preferably, the reaction is carried out at a temperature of 235 to 246°C, a pressure of 0.35 to 0.65 bar, and for a duration of 90 to 130 mins.

[0032] In the present invention, step (2) may be carried out in a single prepolymerization reactor.

[0033] In the present invention, the carboxyl content of the prepolymerization product in step (2) is 40 to 90 mol / t, more preferably 60 to 80 mol / t.

[0034] In the present invention, the polycondensation reaction in step (3) is carried out at a temperature of 235 to 260°C, a pressure of 0.2 to 5 mbar, and a time of 40 to 110 min, and more preferably, the reaction is carried out at a temperature of 238 to 250°C, a pressure of 0.5 to 2 mbar, and a time of 48 to 98 min.

[0035] In the present invention, the carboxyl content of the polycondensation product in step (3) is <50 mol / t, preferably <35 mol / t, and more preferably 10 to 25 mol / t.

[0036] In the present invention, step (3) can be carried out in a finishing apparatus suitable for polycondensation reactions, such as a rotary reactor, a cage reactor, or a horizontal reactor.

[0037] In the present invention, steps (1), (2), and (3) are carried out independently in the presence of a catalyst. The catalysts in steps (1), (2), and (3) are the same or different. The catalyst may be an externally added catalyst or a catalyst present in the system. The catalyst may be a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound, or a titanium compound, more preferably a zinc compound, an aluminum compound, or a titanium compound, most preferably a titanium compound. The titanium compound may be tetrabutyl titanate or tetraisopropyl titanate. Compared to other compounds, titanium compounds have lower residue levels in the product and / or downstream products, and are less toxic. They are particularly suitable for the production of biodegradable polyesters and can be directly introduced into the environment in the form of compost bags or coating films.

[0038] In this invention, the total mass of the reaction raw materials (dibasic acid, diol, and optional crosslinking agent) is 100 wt%, and the total mass of the catalyst is 0.001 to 1 wt%.

[0039] In this invention, other auxiliary agents may be added during the reaction in step (3) depending on the actual needs. These other auxiliary agents include, but are not limited to, catalyst passivators, color stabilizers, and activators.

[0040] The catalyst passivator includes, but is not limited to, a phosphorus compound. The phosphorus compound includes, but is not limited to, one or more of phosphorous acid and phosphoric acid. With a prepolymerization product mass of 100 wt%, the mass of the catalyst passivator is 0.001 to 0.1 wt%, preferably 0.01 to 0.05 wt%. Exemplarily, when a highly active titanium compound is used as the catalyst, a catalyst passivator can be added. Here, the molar ratio of Ti to P is (1.1 to 1.5):1, and particularly preferably, the molar ratio of Ti to P is (1.1 to 1.3):1.

[0041] The color stabilizer includes, but is not limited to, a phosphorus compound. The phosphorus compound includes, but is not limited to, one or more of phosphoric acid, phosphorous acid, triphenyl phosphate, triphenyl phosphate, sodium hypophosphite, and sodium phosphite. The use of a color stabilizer usually reduces the condensation rate. Therefore, triphenyl phosphate is preferably used as a color stabilizer because it does not adversely affect the condensation rate. With a prepolymerization product mass of 100 wt%, the mass of the color stabilizer is 0.001 to 1.5 wt%, preferably 0.01 to 1.0 wt%. When the catalyst is selected from titanium compounds, the molar ratio of Ti to P is 1:(0.3 to 1.0), and particularly preferably the molar ratio of Ti to P is 1:(0.5 to 1.0).

[0042] The activator includes, but is not limited to, a phosphorus compound. The phosphorus compound includes, but is not limited to, one or more of the following: disodium hydrogen phosphate, calcium hypophosphite, calcium phosphite, calcium phosphate, sodium hypophosphite, sodium phosphite, triphenyl phosphite, triphenyl phosphate, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, and tributyl phosphate. With the mass of the prepolymerization product being 100 wt%, the mass of the activator is 0.001 to 1.5 wt%, preferably 0.01 to 1.0 wt%. When the catalyst is selected from titanium compounds, the molar ratio of Ti to P is (1.0 to 1.5):1, particularly preferably (1.1 to 1.3):1.

[0043] More preferably, the color stabilizer and the activator are used in combination, for example, triphenyl phosphate and disodium hydrogen phosphate are used in combination.

[0044] The present invention further includes a chain extension reaction in which, after the polycondensation reaction, the product obtained by the polycondensation reaction (polycondensation product) is reacted with a chain extender to obtain a chain extension product.

[0045] In the present invention, the chain extender comprises one or more of the following: isocyanate, peroxide, epoxide, oxazoline, oxazine, caprolactam, or carbodiimide.

[0046] In the present invention, the isocyanate may be an aromatic diisocyanate and / or an aliphatic diisocyanate, and the aromatic diisocyanate may be toluene 2,4-diisocyanate, toluene 2,6-diisocyanate, diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate, diphenylmethane 4,4'-diisocyanate, 1,5-naphthalene diisocyanate, or xylene diisocyanate, but particularly preferably diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate, or diphenylmethane 4,4'-diisocyanate. The aromatic diisocyanate may be a polynuclear aromatic diisocyanate, for example, tris(4-isocyanatophenyl)methane having three rings that can be formed when producing a diisocyanate having one or two rings. The aliphatic diisocyanate may be a linear or branched alkylene diisocyanate having 2 to 20 carbon atoms, or a cycloalkylene diisocyanate having 3 to 20 carbon atoms. Exemplarily, the aliphatic diisocyanate includes hexamethylene diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate, or methylenebis(4-isocyanetocyclohexane) diisocyanate. Hexamethylene diisocyanate is particularly preferred.

[0047] In the present invention, based on the total mass of the polycondensation product, the mass of the isocyanate may be 0.05 to 2 wt%, but is particularly preferably 0.1 to 1.5 wt%.

[0048] In the present invention, the peroxide may be one or more of the following: benzoyl peroxide, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-butylperoxy)methylcyclododecane, n-butylbis(4,4-tert-butylperoxy)valerate, dicumyl peroxide, tert-butylperoxybenzoate, dibutyl peroxide, α,α-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexa-3-yne, or tert-butylcumeneperoxide.

[0049] In the present invention, based on the total mass of the polycondensation product, the mass of the peroxide may be 0.1 to 2 wt%, but is particularly preferably 0.2 to 1 wt%.

[0050] In the present invention, the epoxide may be one or more copolymers containing epoxy groups based on diglycidyl ether, hexamethylene diglycidyl ether, sorbitol diglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, resorcinol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polybutylene glycol diglycidyl ether, styrene, acrylate and / or methacrylate.

[0051] In this invention, based on the total mass of the polycondensation product, the mass of the epoxide may be 0.1 to 2 wt%, but is preferably 0.2 to 1 wt%.

[0052] In the present invention, the oxazoline may be one or more of the following: 2,2'-bis(2-oxazoline), bis(2-oxazolinyl)methane, 1,2-bis(2-oxazolinyl)ethane, 1,3-bis(2-oxazolinyl)propane, 1,4-bis(2-oxazolinyl)butane, 1,4-bis(2-oxazolinyl)benzene, 1,2-bis(2-oxazolinyl)benzene, or 1,3-bis(2-oxazolinyl)benzene. The oxazine may be one or more selected from 2,2'-bis(2-dioxazine), bis(2-dioxazinyl)methane, 1,2-bis(2-dioxazinyl)ethane, 1,3-bis(2-dioxazinyl)propane, 1,4-bis(2-dioxazinyl)butane, 1,4-bis(2-dioxazinyl)benzene, 1,2-bis(2-dioxazinyl)benzene, or 1,3-bis(2-dioxazinyl)benzene. The carbodiimide may be one or more selected from N,N'-di-2,6-diisopropylphenylcarbodiimide, N,N'-di-o-tolylcarbodiimide, N,N'-diphenylcarbodiimide, N,N'-dioctyldecylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N-tolyl-N'-cyclohexylcarbodiimide, N,N'-di-2,6-di-tert-butylphenylcarbodiimide, N,N'-di-2,4,6-triisobutylphenylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, di-β-naphthylcarbodiimide, or di-tert-butylcarbodiimide.

[0053] In the present invention, based on the total mass of the polycondensation product, the masses of oxazoline, oxazine, caprolactam, and carbodiimide are each independently 0.1 to 2 wt%, preferably 0.2 to 1 wt%.

[0054] In this invention, the temperature of the chain extension reaction is 170 to 245°C, and more preferably, the reaction temperature is 180 to 235°C. Depending on the system used, the reaction is carried out under ultra-high pressure or atmospheric pressure.

[0055] In the present invention, the chain extension reaction can be carried out in an extruder, a continuous kneader (List reactor), or a static mixer. The extruder may be a single-screw or twin-screw extruder. The static mixer can use SMR, SMX, or SMXL components, or a combination thereof. Examples of List reactors include single-screw DISCOTHERM B, twin-screw CRP, or ORP reactors. Preferably, the chain extension reaction is carried out in an extruder, with a residence time of 2 to 15 minutes, more preferably 4 to 13 minutes.

[0056] The present invention further includes a step of slicing the polycondensation product prior to the contact treatment in step (4). The size of the slices is limited by the weight per 100 particles (100-particle weight), where the 100-particle weight after slicing the polycondensation product is 2.2 to 6.0 g, preferably 3.0 to 4.5 g.

[0057] In the present invention, the mass ratio of the polycondensation product to the organic solvent in step (4) is 1:(1 to 10), and may be, for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any of the above values, but more preferably 1:(2 to 6).

[0058] In this invention, organic solvents with a boiling point of 100°C or lower are preferred in order to facilitate the volatilization of organic solvents in subsequent processes and to minimize the residual amount of organic solvents in the polyester product.

[0059] Preferably, the organic solvent comprises at least one of a ketone compound, an alcohol compound, an ether compound, or an aliphatic hydrocarbon compound. The ketone compound includes, but is not limited to, acetone and / or butanone, and is preferably acetone. The alcohol compound includes, but is not limited to, methanol, ethanol, isopropanol, etc. The ether compound includes, but is not limited to, at least one of ethyl ether, propyl ether, and tetrahydrofuran, and is preferably tetrahydrofuran. The aliphatic hydrocarbon compound comprises, but is not limited to, at least one of n-hexane, n-heptane, and cyclohexane, and is preferably n-hexane and / or cyclohexane.

[0060] In this invention, the organic solvent may be a pure organic solvent or an aqueous solution of an organic solvent. When selected from an aqueous solution of an organic solvent, the mass concentration of the aqueous solution of the organic solvent is 35 to 90 wt%.

[0061] In the present invention, the contact treatment in step (4) is performed at a temperature of 35 to 80°C for a duration of 3 to 20 hours, preferably at a temperature of 40 to 55°C for a duration of 8 to 18 hours.

[0062] In this invention, the oligomer content in aliphatic polyester can be controlled by contact treatment. Specifically, the oligomer content can be controlled by controlling the temperature, time, and mass ratio of polycondensation product to organic solvent during contact treatment. If the contact treatment temperature is too high, the evaporation of the organic solvent will be rapid, resulting in increased wear. If the contact treatment temperature is too low, the elution effect will not be effectively obtained, and the oligomer content will be too high. If the contact treatment time is too long, the amount of organic solvent remaining in the polyester will be excessive. If the contact treatment time is too short, the elution effect will not be effectively obtained, and the oligomer content will be excessive. If the mass ratio of polycondensation product to organic solvent is outside the range, i.e., if the amount of organic solvent is excessive, the elution effect can be effectively improved, but solvent consumption will increase, the amount of waste liquid generated will increase, the economic benefit will decrease, and furthermore, the amount of organic solvent remaining in the polyester will be too high. If the content is too low, the polyester cannot be uniformly dispersed in the solution, the elution effect will be non-uniform, and the elution effect will be relatively poor.

[0063] In addition to the contact treatment in step (4), the polymerization conditions and the alcohol-to-acid ratio in steps (1) to (3) all affect the oligomer content.

[0064] In the present invention, the aliphatic polyester can be produced by contact treatment of the polycondensation product, by a chain extension reaction (i.e., a chain growth reaction) of the polycondensation product, or by first extending the chain of the polycondensation product and then contact treatment.

[0065] In the present invention, the aliphatic polyester can also be produced by the following method. That is, in step (1), succinic acid and / or a succinic acid derivative and sebacic acid and / or a sebacic acid derivative are reacted with 1,4-butanediol to obtain two esterified products, and then the two esterified products are subjected to subsequent prepolymerization reactions, polycondensation reactions, and optional chain extension reactions and contact treatments.

[0066] For example, the manufacturing method specifically includes the following steps:

[0067] Step (1-1): Succinic acid and / or succinic acid derivatives, 1,4-butanediol, and an optional crosslinking agent are reacted for 2 to 6 hours under conditions of a temperature of 150 to 195°C and a pressure of 0.7 to 1.2 bar to obtain esterification product A.

[0068] Step (1-2): Sebacic acid and / or a sebacic acid derivative is reacted with 1,4-butanediol at a temperature of 180-220°C and a pressure of 0.6-1.1 bar for 2-6 hours to obtain esterification product B. Then, esterification product A and esterification product B are mixed and subjected to a prepolymerization reaction, polycondensation reaction, and any chain extension reaction or contact treatment. Here, the conditions for the prepolymerization reaction, polycondensation reaction, and any chain extension reaction or contact treatment are selected from the same range as in Step (2), Step (3), the aforementioned chain extension reaction, and Step (4).

[0069] In a second aspect, the present invention provides a polyester composition comprising the aliphatic polyester described in the first aspect.

[0070] Preferably, the polyester composition comprises at least one of a second polyester, a third polymer, and an auxiliary agent.

[0071] Preferably, the second polyester comprises at least one of polylactic acid, aliphatic-aromatic polyester, or other aliphatic polyester.

[0072] Preferably, the second polyester comprises at least one of polylactic acid (PLA), aliphatic-aromatic polyester, or other aliphatic polyester.

[0073] Preferably, the aliphatic-aromatic polyester comprises at least one of the following: polybutylene succinate terephthalate (PBST), polybutylene adipate terephthalate (PBAT), polybutylene sebacate terephthalate (PBSeT), or polybutylene adipate diflangecarboxylate (PBAF).

[0074] Preferably, the other aliphatic polyester comprises at least one of polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), or polybutylene sebacate (PBSe).

[0075] In this invention, in accordance with the standard ISO 1133-2-2012, the melt flow rate of the second polyester is 0.5 to 50 g / 10 min under conditions of 190°C and 2.16 kg.

[0076] In the present invention, the second polyester can be selected according to the actual needs and is not limited to the polyester described above.

[0077] Preferably, the third polymer comprises at least one of the following: starch, cellulose, chitin, chitosan, alginate ester, protein, gelatin, natural rubber, lignin, or a derivative of one of the aforementioned substances.

[0078] In this invention, the protein includes, but is not limited to, gluten, zein, casein, and collagen. The lignin includes unrefined lignin, purified hydrolyzed lignin, alkalized lignin, and the like. Starch can be used in allosteric form, gelled form, or filler form. The starch may represent a continuous phase or a dispersed phase, or it may be in a cocontinuous form.

[0079] In the present invention, the auxiliary agent may be added according to the actual needs and may include, but is not limited to, at least one of the following: an antioxidant, a lubricant, a light stabilizer, a mold release agent, or an antistatic agent.

[0080] In the present invention, the type of auxiliary agent is not particularly limited, and any ordinary auxiliary agent may be used. For example, the antioxidant includes, but is not limited to, any one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 164, antioxidant DLTP, or antioxidant TPP.

[0081] The aforementioned light stabilizer includes, but is not limited to, at least one of the following: a hindered amine light stabilizer (e.g., light stabilizer 770, light stabilizer 622, light stabilizer 944, etc.), a benzophenone light stabilizer (e.g., UV531), or a benzotriazole light stabilizer.

[0082] The lubricant includes, but is not limited to, at least one of esters (e.g., polyethylene glycol esters, polyol esters), montanates, ethylenebisstearamide, or polyethylene wax.

[0083] The aforementioned release agent includes, but is not limited to, at least one of the following: inorganic release agents (e.g., talc powder, mica powder, clay, etc.), organic release agents (e.g., fatty acids, paraffin, glycerol, petrolatum, etc.), or polymeric release agents (e.g., silicone oil, polyethylene glycol, low molecular weight polyethylene, etc.).

[0084] The antistatic agent includes, but is not limited to, at least one of the following: a cationic antistatic agent (e.g., a quaternary ammonium salt), an anionic antistatic agent (e.g., alkyl sulfonates, phosphates), an amphoteric antistatic agent (e.g., an amphoteric imidazoline compound), a nonionic antistatic agent (e.g., hydroxyethylalkylamines, fatty acid amides, polyoxyethylenes, polyol esters), or a polymeric antistatic agent (e.g., polyethers).

[0085] As a preferred technical solution of the present invention, the polyester composition comprises, by weight, 50 to 95 parts by weight of aliphatic polyester (for example, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or any number in between, but preferably 52 to 92 parts, more preferably 56 to 82 parts) and 1 to 20 parts by weight of a second polyester (for example, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, or any number in between, but preferably The mixture comprises 1.5 to 15 parts, more preferably 2.5 to 8.5 parts, a third polymer, 1 to 30 parts (for example, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 25, 26, 28, 30 parts, or any number in between, but preferably 9 to 27 parts, more preferably 21 to 26.5 parts), and an auxiliary agent, 0 to 15 parts (for example, 1, 2, 4, 6, 8, 10, 12, 14, 15 parts, or any number in between).

[0086] In the present invention, the method for producing the polyester composition includes the steps of mixing an aliphatic polyester with an optional second polyester, a third polymer, and an auxiliary agent, and extruding the mixture to obtain the polyester composition, wherein the extruder includes a reaction extruder, which may be a single-screw extruder, a twin-screw extruder, or a multi-screw extruder, the extrusion temperature is 140 to 220°C, and the screw rotation speed during extrusion is 200 to 500 rpm.

[0087] In a third aspect, the present invention provides a packaging film, wherein the raw materials for manufacturing the packaging film include the aliphatic polyester described in the first aspect or the polyester composition described in the second aspect.

[0088] In the present invention, the raw materials for manufacturing the packaging film may include other substances such as colorants, pigments, and inorganic fillers, depending on the actual needs. The pigments include, but are not limited to, titanium dioxide, and the inorganic fillers include, but are not limited to, talc powder, calcium carbonate, and kaolin.

[0089] Preferably, the unwinding index of the packaging film is ≤3, more preferably ≤2.5, more preferably ≤2, and most preferably ≤1.5.

[0090] Preferably, in accordance with standard EU10-2011 and OM6 test conditions, with 10% ethanol as the simulated solution and a packaging film thickness of 18±2 μm, the total migration amount of the packaging film is ≤10 mg / dm 2 More preferably, the total transfer amount is ≤5 mg / dm 2 That is the case.

[0091] In the present invention, the packaging film includes plastic wrap, shrink wrap, and wrap film.

[0092] The aliphatic polyester, the polyester composition containing the aliphatic polyester, and the packaging film made from these are all biodegradable.

[0093] In this invention, a substance or mixture of substances is considered to have the characteristic of "biodegradability" if it exhibits a biodegradability rate of at least 90%, as defined in DIN EN 13432.

[0094] According to DIN EN 13432, the composting process involves introducing CO2-free air into the maturing compost and subjecting it to specific temperature treatments. Here, biodegradability is defined as the biodegradation rate, expressed as the ratio of the net amount of CO2 released from the sample (minus the amount of CO2 released from compost without the sample) to the maximum amount of CO2 that the sample can release (calculated from the carbon content in the sample). Biodegradable polyesters and biodegradable polyester compositions typically show clear signs of decomposition, such as fungal growth, dissolution, and perforation, within just a few days after composting.

[0095] Other methods for determining biodegradability are also described in ASTM D5338 and ASTM D6400.

[0096] The numerical range described in this invention includes not only the point values ​​listed above, but also all point values ​​within the numerical range not listed above. Due to space limitations and for the sake of brevity, this invention does not exhaustively list all specific point values ​​included in the range. [Effects of the Invention]

[0097] Compared to conventional technology, the beneficial effects of the present invention are as follows:

[0098] In the aliphatic polyester according to the present invention, by controlling the molar ratio of succinic acid and sebacic acid within a specific range, and by controlling the oligomer content in the aliphatic polyester within a specific range, the packaging film containing the aliphatic polyester possesses good unwinding properties and food contact characteristics, while simultaneously having good biodegradability and meeting requirements such as composting at home. [Modes for carrying out the invention]

[0099] The technical solutions of the present invention will be further described below through specific embodiments. Those skilled in the art will understand that the embodiments described are merely to aid in understanding the present invention and should not be construed as particularly limiting the invention.

[0100] In this invention, all materials used can be purchased commercially or prepared using conventional methods. Unless otherwise specified, the materials used in this invention are as follows: 1,4-Butanediol: Purchased from Xinjiang MarkorChem Co., Ltd. Succinic acid: Purchased from Shandong Lanzian Biotechnology Co., Ltd. Sebacic acid: Purchased from Hengshui Jinghua Chemical Co., Ltd. Glycerol: Purchased from Aladdin. Tetrabutyl titanate: Purchased from Jianyi Chemical Import & Export Co., Ltd. Hexamethylene diisocyanate: Purchased from Aladdin.

[0101] In this invention, the method for testing the mole fraction, number-average molecular weight (Mn), oligomer content, intrinsic viscosity, and carboxyl content of succinic acid residues and sebacic acid residues in an aliphatic polyester is as follows.

[0102] 1. The mole fractions of succinic acid residues and sebacic acid residues in aliphatic polyesters are: 1 The sample can be tested by 1H NMR. Specifically, 20 mg of the aliphatic polyester sample is dissolved in 0.6 mL of deuterated chloroform, and then the sample is analyzed at room temperature using a Bruker AV 500 NMR spectrometer. 1¹H NMR is measured. The characteristic chemical shiff peaks of succinic acid residues and sebacic acid residues are integrated, and the mole fractions of succinic acid residues and sebacic acid residues in the aliphatic polyester are obtained from the ratio of peak areas. Note that the content of succinic acid residues and sebacic acid residues in the aliphatic polyester shown in Table 1 is the content when the total molar amount of succinic acid and sebacic acid residues is set to 100 mol%. For example, if the integrated area of ​​succinic acid residues is I1 and the integrated area of ​​sebacic acid residues is I2, then the mole fraction of succinic acid residues in the aliphatic polyester is I1 / (I1+I2)×100%. Here, the characteristic chemical shiff of succinic acid residues is approximately 2.63 ppm, representing the four hydrogen atoms on the two methylene-CH2-CH2- groups in succinic acid. The characteristic chemical schiff of the sebacic acid residue is approximately 1.30 ppm, representing the eight hydrogen atoms on the four methylene-CH2-CH2-CH2-CH2- in the center of sebacic acid.

[0103] 2. Mn and oligomer content are tested using gel permeation chromatography (GPC). A chromatography system is used, employing three tandem columns (particle size 5 μm, porosity 500 Å, 1000 Å, and 10000 Å, respectively) and a refractive index detector, at 40°C, with chloroform as the eluent (elution flow rate 1 mL / min) and polystyrene as the standard substance. The instrument model is Waters 1515GPC. Sample preparation involves directly dissolving aliphatic polyester in chromatography-grade THF to prepare a 1 mg / mL solution for testing.

[0104] 3. The intrinsic viscosity test shall be performed in accordance with standard GB / T 17931-1999. Specifically, 0.1250 ± 0.0002 g of the sample shall be added to 25 mL of a phenol / o-dichlorobenzene mixed solution in a weight ratio of 1:1, heated until the sample is completely dissolved, and then tested using an Ubbelohde viscometer at a test temperature of 25 ± 0.05 °C.

[0105] 4. The carboxyl content test is performed in reference to standard GB / T 32366-2015. Specifically, it is performed as follows: Dissolve 1 g of the sample in 50 mL of a mixed solvent of phenol and chloroform in a volume ratio of 2:3. Use a 0.01 mol / L potassium hydroxide ethanol solution as the standard titration solution and a 0.2% bromophenol blue solution as the indicator. Perform a blank test based on the above method for testing the carboxyl content of the sample. Test the sample twice in parallel, and the difference between the two test results must be 2 mol / t or less. The final result is the average of the two test results. Examples 1-16, Comparative Examples 1-6

[0106] Examples 1-16 and Comparative Examples 1-6 each provide aliphatic polyesters. The molecular structure composition, q1 value, q2 value, carboxyl content, and intrinsic viscosity of the aliphatic polyesters are shown in Table 1.

[0107] [Table 1]

[0108] The methods for producing aliphatic polyesters according to Examples 1-16 and Comparative Examples 1-6 are as follows. Example 1

[0109] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 479 kg of succinic acid, 116 kg of sebacic acid, 560 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3.5 hours at a temperature of 200°C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.48 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 120 min at a temperature of 240°C and a pressure of 0.52 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 90 minutes at a temperature of 243°C and a pressure of 1.3 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) was sliced, and the weight of 100 slices was set to approximately 3.7 g. This was then subjected to a contact treatment with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:5, the mass concentration of the aqueous tetrahydrofuran solution was 70%, the contact treatment temperature was 50°C, and the contact treatment time was 14 h. The aliphatic polyester was obtained. Example 2

[0110] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 433 kg of succinic acid, 162 kg of sebacic acid, 570 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 190°C and a pressure of 0.9 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.48 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 110 min at a temperature of 243°C and a pressure of 0.45 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 80 minutes at a temperature of 243°C and a pressure of 1.1 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) was sliced, and the weight of 100 slices was made to approximately 3.7 g. This was then subjected to a contact treatment with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:5, the mass concentration of the aqueous tetrahydrofuran solution was 65%, the contact treatment temperature was 55°C, and the contact treatment time was 14 h. The aliphatic polyester was obtained. Example 3

[0111] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 388 kg of succinic acid, 215 kg of sebacic acid, 560 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 205°C and a pressure of 1.0 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.48 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 95 minutes at a temperature of 238°C and a pressure of 0.40 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 80 minutes at a temperature of 242°C and a pressure of 1.0 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) was sliced, and the weight of 100 slices was set to approximately 3.7 g. This was then subjected to a contact treatment with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:5, the mass concentration of the aqueous tetrahydrofuran solution was 70%, the contact treatment temperature was 50°C, and the contact treatment time was 14 h. The aliphatic polyester was obtained. Example 4

[0112] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 350 kg of succinic acid, 250 kg of sebacic acid, 534 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3.5 hours at a temperature of 200°C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.48 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 100 min at a temperature of 242°C and a pressure of 0.4 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 85 minutes at a temperature of 242°C and a pressure of 1.1 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) was sliced, and the weight of 100 slices was set to approximately 3.7 g. This was then subjected to a contact treatment with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:5, the mass concentration of the aqueous tetrahydrofuran solution was 70%, the contact treatment temperature was 50°C, and the contact treatment time was 14 h. The aliphatic polyester was obtained. Example 5

[0113] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 320 kg of succinic acid, 280 kg of sebacic acid, 534 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3 hours at a temperature of 180°C and a pressure of 0.8 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.48 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 110 min at a temperature of 243°C and a pressure of 0.60 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 90 minutes at a temperature of 243°C and a pressure of 1.3 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) was sliced, and the weight of 100 slices was set to approximately 3.7 g. This was then subjected to a contact treatment with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:4, the mass concentration of the aqueous tetrahydrofuran solution was 60%, the contact treatment temperature was 45°C, and the contact treatment time was 12 h. The aliphatic polyester was obtained. Example 6

[0114] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows. In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 60 minutes at a temperature of 240°C and a pressure of 1.4 mbar to obtain a polycondensation product. Then, the polycondensation product and hexamethylene diisocyanate (content: 0.20 wt% of the mass of the polycondensation product) were extruded in a reaction extruder at a temperature of 200°C for a residence time of 7 minutes to obtain slices of chain extension product with a weight of approximately 3.7 g per 100 particles. In step (4), the chain extension product slices obtained were subjected to a contact treatment with an aqueous tetrahydrofuran solution. Here, the mass ratio of the chain extension product slices to the aqueous tetrahydrofuran solution was 1:6, the mass concentration of the aqueous tetrahydrofuran solution was 80%, the contact treatment temperature was 50°C, and the contact treatment time was 15 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 4. Example 7

[0115] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows: In step (4), the polycondensation product obtained in step (3) was sliced, and the weight of 100 particles of the slice was made to approximately 3.7 g, and the slices were brought into contact with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product slices to the aqueous tetrahydrofuran solution was 1:8, the mass concentration of the aqueous tetrahydrofuran solution was 85%, the contact treatment temperature was 55°C, and the contact treatment time was 16 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 4. Example 8

[0116] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows: In step (4), the polycondensation product obtained in step (3) was sliced, and the weight of 100 particles of the slice was made to approximately 3.7 g, and the slices were brought into contact with an aqueous acetone solution. Here, the mass ratio of the polycondensation product to the aqueous acetone solution was 1:5, the mass concentration of the aqueous acetone solution was 75%, the contact treatment temperature was 45°C, and the contact treatment time was 12 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 4. Example 9

[0117] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows: In step (4), the polycondensation product obtained in step (3) was sliced, and the weight of 100 particles of the slice was made to approximately 3.7 g, and the slices were brought into contact with an aqueous ethanol solution. Here, the mass ratio of the polycondensation product to the aqueous ethanol solution was 1:5, the mass concentration of the aqueous ethanol solution was 80%, the contact treatment temperature was 70°C, and the contact treatment time was 18 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 4. Example 10

[0118] A method for producing the aliphatic polyester is provided, comprising the following steps. (1) 350 kg of succinic acid, 250 kg of sebacic acid, 534 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 2.5 hours at a temperature of 180°C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.48 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 100 min at a temperature of 240°C and a pressure of 0.45 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 95 minutes at a temperature of 245°C and a pressure of 1.3 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) was sliced, and the weight of 100 slices was made to approximately 4.4 g. This was then subjected to a contact treatment with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:3, the mass concentration of the aqueous tetrahydrofuran solution was 75%, the contact treatment temperature was 55°C, and the contact treatment time was 12 h. The aliphatic polyester was obtained. Example 11

[0119] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows. In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 85 minutes at a temperature of 242°C and a pressure of 1.1 mbar to obtain a polycondensation product. In step (4), the polycondensation product obtained in step (3) was sliced, and the weight of 100 particles of the slice was made to be approximately 3.7 g, and a contact treatment was performed with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:7, the mass concentration of the aqueous tetrahydrofuran solution was 75%, the contact treatment temperature was 55°C, and the contact treatment time was 14 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 4. Example 12

[0120] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows. In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 50 minutes at a temperature of 246°C and a pressure of 1.4 mbar to obtain a polycondensation product. The polycondensation product and hexamethylene diisocyanate (content: 0.55 wt% of the mass of the polycondensation product) were extruded in a reaction extruder at a temperature of 210°C for a residence time of 9 minutes to obtain chain extension product slices. In step (4), the chain extension product obtained in step (3) was sliced, and the weight of 100 particles of the slices was set to approximately 4.0 g, and a contact treatment with an aqueous ethanol solution was performed. Here, the mass ratio of the chain extension product slices to the aqueous ethanol solution was 1:4, the mass concentration of the aqueous ethanol solution was 70%, the contact treatment temperature was 50°C, and the contact treatment time was 12 h. The aliphatic polyester was obtained. The remaining ingredients, quantities used, and manufacturing method were all the same as in Example 4. Example 13

[0121] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows. (1-1) 350 kg of succinic acid, 290 kg of 1,4-butanediol, and 2.76 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 170°C and a pressure of 1.1 bar to obtain esterification product A. (1-2) 245 kg of sebacic acid and 260 kg of 1,4-butanediol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3 hours at a temperature of 210°C and a pressure of 1.0 bar to obtain esterification product B. After mixing esterification product A and esterification product B, steps (2), (3), and (4) were carried out. The remaining raw materials, quantities used, and manufacturing methods were all the same as in Example 4. Example 14

[0122] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows: In step (4), the polycondensation product obtained in step (3) was sliced, and the weight of 100 particles of the slice was made to approximately 3.7 g, and the slices were brought into contact with a cyclohexane solution. Here, the mass ratio of the polycondensation product to the cyclohexane solution was 1:8, the mass concentration of the cyclohexane solution was 100%, the contact treatment temperature was 70°C, and the contact treatment time was 16 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 4. Example 15

[0123] A method for producing the aliphatic polyester is provided, comprising the following steps. (1-1) 350 kg of succinic acid, 310 kg of 1,4-butanediol, and 3.25 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 190°C and a pressure of 0.9 bar to obtain esterification product A. (1-2) 245 kg of sebacic acid and 290 kg of 1,4-butanediol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 210°C and a pressure of 0.8 bar to obtain esterification product B. (2) The esterification product A obtained in step (1-1) and the esterification product B obtained in step (1-2) were transferred to a vertical reactor with a stirring function, 0.48 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 100 min at a temperature of 240°C and a pressure of 0.5 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 90 minutes at a temperature of 245°C and a pressure of 1.0 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) was sliced, and the weight of 100 slices was made to approximately 3.2 g. This was then subjected to contact treatment with a tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the tetrahydrofuran solution was 1:6, the mass concentration of the tetrahydrofuran solution was 100%, the contact treatment temperature was 55°C, and the contact treatment time was 18 h. The aliphatic polyester was obtained. Example 16

[0124] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows. In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 70 minutes at a temperature of 242°C and a pressure of 1.4 mbar to obtain a polycondensation product. The polycondensation product and hexamethylene diisocyanate (content: 0.72 wt% of the mass of the polycondensation product) were extruded in a reaction extruder at a temperature of 230°C for a residence time of 12 minutes to obtain chain extension product slices. In step (4), the obtained chain extension product was sliced, and the weight of 100 particles of the slices was set to approximately 4.4 g, and a contact treatment was performed with an aqueous ethanol solution. Here, the mass ratio of chain extension product slices to aqueous ethanol solution was 1:4, the mass concentration of the aqueous ethanol solution was 65%, the contact treatment temperature was 65°C, and the contact treatment time was 10 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 4. Comparative Example 1

[0125] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows: Step (4) was not performed. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 4. Comparative Example 2

[0126] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows. In step (4), the polycondensation product obtained in step (3) was sliced, and the weight of 100 particles of the slice was made to approximately 3.7 g, and the slices were brought into contact with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:10, the mass concentration of the aqueous tetrahydrofuran solution was 85%, the contact treatment temperature was 55°C, and the contact treatment time was 20 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Example 4. Comparative Example 3

[0127] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 275 kg of succinic acid, 315 kg of sebacic acid, 534 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3 hours at a temperature of 200°C and a pressure of 1.0 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.48 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 115 min at a temperature of 240°C and a pressure of 0.70 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 100 minutes at a temperature of 246°C and a pressure of 1.1 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) was sliced, and the weight of 100 slices was set to approximately 3.7 g. This was then subjected to a contact treatment with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:5, the mass concentration of the aqueous tetrahydrofuran solution was 70%, the contact treatment temperature was 50°C, and the contact treatment time was 14 h. The aliphatic polyester was obtained. Comparative Example 4

[0128] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 535 kg of succinic acid, 60 kg of sebacic acid, 534 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3.5 hours at a temperature of 200°C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.48 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 120 min at a temperature of 243°C and a pressure of 0.50 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 90 minutes at a temperature of 245°C and a pressure of 1.2 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) was sliced, and the weight of 100 slices was set to approximately 3.7 g. This was then subjected to a contact treatment with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:5, the mass concentration of the aqueous tetrahydrofuran solution was 70%, the contact treatment temperature was 50°C, and the contact treatment time was 14 h. The aliphatic polyester was obtained. Comparative Example 5

[0129] A method for producing the aliphatic polyester is provided. The differences from Comparative Example 3 are as follows. In step (4), the polycondensation product obtained in step (3) was sliced, and the weight of 100 particles of the slice was made to approximately 3.2 g, and the slices were brought into contact with an aqueous tetrahydrofuran solution. Here, the mass ratio of the polycondensation product to the aqueous tetrahydrofuran solution was 1:8, the mass concentration of the aqueous tetrahydrofuran solution was 90%, the contact treatment temperature was 55°C, and the contact treatment time was 16 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Comparative Example 3. Comparative Example 6

[0130] A method for producing the aliphatic polyester is provided. The differences from Comparative Example 4 are as follows. In step (4), the polycondensation product obtained in step (3) was sliced, and the weight of 100 particles of the slice was made to approximately 3.0 g, and the slices were brought into contact with an aqueous ethanol solution. Here, the mass ratio of the polycondensation product to the aqueous ethanol solution was 1:8, the mass concentration of the aqueous ethanol solution was 70%, the contact treatment temperature was 70°C, and the contact treatment time was 18 h. The aliphatic polyester was obtained. The remaining raw materials, amounts used, and manufacturing method were all the same as in Comparative Example 4. Performance testing

[0131] The aliphatic polyesters from Examples 1-16 and Comparative Examples 1-6 were cast as follows to obtain wrap films.

[0132] Screw temperature: 145~150℃, die head temperature: 165℃, cooling temperature: 10℃, main feed speed: 27.2kg / h, traction roller: 11.5Hz, winding roller: 11.8~13.2Hz.

[0133] The unwinding properties, food contact characteristics, and decomposition cycle of the obtained wrap film were tested.

[0134] In this invention, the method for evaluating the rewind index is as follows: Approximately 10 cm of a wound-up film roll (30 cm wide, 10 ± 2 μm thick) was peeled off, and the film was lifted to a height of 1 m using both hands, allowing the film roll to freefall. The rewind index was evaluated by the time it took for the film to fall to the ground. Here, a rewind index of 1.0 resulted in freefall within 1 s. A rewind index of 1.5 resulted in freefall within 3 s. A rewind index of 2.0 resulted in freefall within 5 s. A rewind index of 2.5 resulted in freefall within 7 s. A rewind index of 3.0 resulted in freefall within 10 s. A rewind index of 4.0 resulted in freefall within 15 s. A rewind index of 5.0 resulted in freefall within 20 s. A lower rewind index indicated better rewindability.

[0135] In this invention, the food contact characteristics can be expressed by the amount of oligomer migration in the wrap film. Specifically, in accordance with standard EU10-2011, the amount of migration was tested under OM6 test conditions, using 10% ethanol as a simulated solution and a wrap film thickness of 18±2 μm. Decomposition period:

[0136] The aliphatic polyester was molded into a product measuring 10 cm x 10 cm with a thickness of 18 ± 2 μm. A composting test was conducted in a home setting in accordance with standard AS5810-2010, and the biodegradation rate after 16 weeks of composting was recorded.

[0137] The specific test results are shown in Table 2.

[0138] [Table 2]

[0139] As can be seen from Table 2, by adjusting the ratio of succinic acid residues to sebacic acid residues and controlling the oligomer content within a specific range, the aliphatic polyester of the present invention can provide a packaging film containing the aliphatic polyester that combines good food contact properties and unwinding properties, and furthermore, under home composting conditions, it has high biodegradability and meets the requirements for home composting.

[0140] The specific embodiments described above further illustrate the object, technical solution, and beneficial effects of the present invention. These are merely specific embodiments of the present invention and do not limit it. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are also covered by the present invention.

Claims

1. An aliphatic polyester comprising a dibasic acid residue and a diol residue, The aforementioned dibasic acid residue is, as a residue, a1): Based on the total mole fraction of a1) and a2) of 100 mol%, 65-90 mol% succinic acid residues, a2): Based on the total mole fraction of a1) and a2), it contains 10 to 35 mol% of sebaciate residues, The aforementioned diol residue is selected from at least a dibasic acid residue and an equimolar amount of a 1,4-butanediol residue. The aliphatic polyester is characterized in that it contains oligomers with a number average molecular weight < 1000 as measured by GPC, and the mass fraction of the oligomers with a number average molecular weight < 1000 as measured by GPC is 0.08 to 3.45 wt%.

2. In the aliphatic polyester, the oligomers with a number-average molecular weight < 1000, as measured by GPC, have the following characteristics: 0.05wt%<q 1 <1.0045 0.1wt%<q 2 <2.5wt% Here, q 1 This is the mass fraction of oligomers with a number-average molecular weight of less than 500 in aliphatic polyesters, as measured by GPC. q 2 This is the mass fraction of oligomers with a number-average molecular weight of less than 1000 in aliphatic polyesters, as measured by GPC. Preferably, the q 1 It is 0.1 to 0.6 wt%, Preferably, the q 2 The aliphatic polyester according to claim 1, characterized in that the amount is 0.2 to 1.3 wt%.

3. the aforementioned q 2 and q 1 is < 2, and preferably, q 2 and q 1 is < 1.5, the aliphatic polyester according to claim 2.

4. The aforementioned dibasic acid residue is, as a residue, a1): Based on the total mole fraction of a1) and a2) at 100 mol%, 74-85 mol% succinic acid residues, a2): The aliphatic polyester according to claim 1, characterized in that it contains 15 to 26 mol% of sebaciate residues based on a total mole fraction of 100 mol% of a1) and a2).

5. The aliphatic polyester according to claim 1, characterized in that, in accordance with GB / T 32366-2015, the carboxyl content of the aliphatic polyester is <40 mol / t, more preferably <30 mol / t, and more preferably <22 mol / t.

6. The aliphatic polyester according to claim 1, characterized in that, in accordance with GB / T 17931-1999, the intrinsic viscosity of the aliphatic polyester is 1 to 3 dL / g.

7. A polyester composition, characterized in that the polyester composition comprises the aliphatic polyester described in claim 1.

8. The polyester composition further comprises at least one of a second polyester, a third polymer, and an auxiliary agent. Preferably, the second polyester comprises at least one of polylactic acid, aliphatic-aromatic polyester, or other aliphatic polyester. Preferably, the aliphatic-aromatic polyester comprises at least one of polybutylene succinate terephthalate, polybutylene adipate terephthalate, polybutylene sebacate terephthalate, or polybutylene adipate difrangiccarboxylate. Preferably, the other aliphatic polyester comprises at least one of polybutylene succinate, polybutylene succinate adipate, or polybutylene sebacate. Preferably, the polyester composition according to claim 7, wherein the third polymer comprises at least one of the following: starch, cellulose, chitin, chitosan, alginate ester, protein, gelatin, natural rubber, lignin, or a derivative of the aforementioned substances.

9. A packaging film, wherein the raw materials for manufacturing the packaging film include an aliphatic polyester according to any one of claims 1 to 6, or a polyester composition according to claim 7 or 8.

10. The unwinding index of the aforementioned packaging film is ≤ 3. Preferably, in accordance with standard EU10-2011 and OM6 test conditions, with 10% ethanol as the simulated solution and a packaging film thickness of 18 ± 2 μm, the total migration amount of the packaging film is ≤ 10 mg / dm 2 The packaging film according to claim 9, characterized in that it is the packaging film according to claim 9.